Shear performance and reinforcement mechanism of MICP-treated single fractured sandstone - Yao, Xiao; Huafeng, Deng; Jianlin, Li; Xingzhou, Chen (Frontiers in Earth Science, 2022)
There are a large number of fractured rock masses in the Three Gorges Reservoir area. The traditional reinforcement methods have disadvantages such as large engineering investment, high material consumption, and poor ecological environmental protection. Therefore, it is necessary to develop new environmentally friendly materials and methods to strengthen and control them. The microbial induced carbonate precipitation (MICP) technology that has emerged in recent years has the characteristics of low carbon, environmental protection and has great prospects in the restoration and reinforcement of rock and soil materials. Therefore, Bacillus cereus extracted in situ of Three Gorges Reservoir area is proposed to be used for MICP reinforcement of single-fractured sandstone, and its reinforcement mechanism is revealed by studying the macroscopic impermeability and shear performance improvement of the fractured rock sample after reinforcement, as well as the microstructure changes. The results show that after 10 cycles of grouting reinforcement, the fracture surface of the rock sample is well sealed, the permeability coefficient is reduced by two orders of magnitude, the shear stress is increased by 26%~40%, and the shear stiffness is increased by 70%. Above, the shear stress-shear displacement curve shows the peak shear strength, and the residual shear strength also increases to a certain extent. The MICP process improves the mechanical properties of fractured rock samples from three aspects, namely, the cementation between sand grains and the fracture surface, the cementation effect between sand grains and the filling effect of fractured rock samples. The shear failure surface of the samples after reinforcement is the recheck interface between the cementation body and the cementation interface. The relevant research results can provide reference for the MICP reinforcement technology of fractured rock mass.